The Relationship Between Knowledge And Attitudes Towards Fish-Consuming Behavior In Community Affected By Covid-19 In Cimanggis Depok - Rubi Isfahani, Wita; Rusilanti, Rusilanti; Alsuhendra, Alsuhendra (Devotion : Journal of Research and Community Service, 2022)
Fish is a product of natural resources with high economic and biological value. One of the benefits of fish is  its nutrient that can increase immunity. However, fish to the public and have not been consumed evenly in Indonesia. This study aims to determine the relationship between knowledge and attitudes about fish consumption on society’s fish consumption behavior. The type of research is quantitative with a survey approach. The sample in this study was the community affected by the covid-19 pandemic in the Cimanggis district, Depok city with a total sample of 25 respondents who were selected by random sampling technique. The research data were analyzed using descriptive analysis and inferential analysis. The results showed that the percentage of 25 respondents who had high fish knowledge was 64%, respondents who had high fish consumption attitudes were 72%, and 64% of respondents had low fish consumption behavior. Meanwhile, the results of the correlation test showed that there was no relationship between knowledge and fish-consuming behavior (r= 0,160) and there was no relationship between attitude and fish-consuming behavior (r = 0,395). Based on the research results, it is expected that the community, educators and the government can create and implement programs that can increase fish consumption, thus society would have excellent immunity.